High Levels of Soluble C5b-9 Complex in Dialysis Fluid May Predict Poor Prognosis in Peritonitis in Peritoneal Dialysis Patients - Mizuno, Masashi; Suzuki, Yasuhiro; Higashide, Keiko; Sei, Yumi; Iguchi, Daiki; Sakata, Fumiko; Horie, Masanobu; Maruyama, Shoichi; Matsuo, Seiichi; Morgan, B. Paul; Ito, Yasuhiko (PLOS ONE, 2017)
Background We searched for indicators to predict the prognosis of infectious peritonitis by measuring levels of complement proteins and activation products in peritoneal dialysis (PD) fluid (PDF) of patients at early stages of peritonitis. We retrospectively analyzed the relationship between the levels of sC5b-9, C3 and C4 in PDF and the subsequent clinical prognosis. Methods We measured levels of sC5b-9, C3 and C4 in PDF on days 1, 2 and 5 post-onset of peritonitis in 104 episodes of infectious peritonitis in PD patients from 2008 and retrospectively compared levels with clinical outcomes. Further analysis for the presence of causative microorganisms or to demonstrate bacterial culture negative peritonitis was performed and correlated with change of levels of sC5b-9 in PDF. Results When PD patients with peritonitis were divided into groups that either failed to recover from peritonitis and were finally withdrawn from PD (group 1; n = 25) or recovered (group 2; n = 79), levels of sC5b-9, C3 and C4 in PDF were significantly higher in group 1 patients compared to those in group 2 on day5. Analysis of microorganisms showed significantly higher sC5b-9 levels in PDF of peritonitis cases caused by culture negative peritonitis in group 1 compared with group 2 when we analyzed for individual microorganisms. Of note, on day5, the sC5b-9 levels in PDF were similarly high in peritonitis caused by fungi or other organisms. Conclusion Our results suggested that levels of complement markers in PDF, especially sC5b-9, have potential as surrogate markers to predict prognosis of PD-related peritonitis.